As contribuições dos conhecimentos populares, na dimensão da espiritualidade, no processo de formação de professores do Programa de Extensão Tecelendo da UFRB - Delfino, Elisabete Ferreira (2019)
The present work of dissertation is the result of a research that had as its central theme the contributions of popular knowledge regarding the dimension of spirituality, in a process of teacher training in the perspective of popular education. This research work arises from the concerns experienced in the process of formation of educators in the Tecelendo Extension Program at the Universidade Federal do Recôncavo da Bahia, of which I am a part since the year 2009. Treat the contributions of spirituality in the training of teachers is a big challenge. However, the contributions of popular education in Brazil bring us to an important debate regarding the dimension of spirituality in the processes of teacher training. In this sense, we developed a qualitative research with a focus on research participant. The instruments used were: 1) semi-structured interviews with 15 teachers and educators of Tecelendo; 2) participant observation of teacher training activities developed by the program; 3) analysis of documents of Tecelendo. The research revealed that the spirituality is present in the formation of educators Tecelendo from popular knowledge and of mysticism involved for them, moreover, it was possible to perceive its contribution in the process of transformation and emancipation of the educators and teachers included in the program. The theoretical reference of this work is based on studies of: Paulo Freire (1996 and 2014), João Francisco de Souza (2007), Eymard Vasconcellos (2009), Ferdinando Röhr (2013), Fritjot Capra (2014); Leonardo Boff (2006, 2008) and Frei Betto (2008). The contributions of this research work go on extension of the dialog between Popular Education and spirituality in teacher training, as well as with a probable elements for reflection and improvement of methodologies in Tecelendo Extension Program.